Bridging Cultures through Numbers: Exploring the Perspectives of Pre-Service Mathematics Teachers on Ethnomathematics in Education - Justin Ian Ogoy; Jhaynee Lou Tudayan-Del Moral (Southeast Asian Mathematics Education Journal, 2026)
The growing emphasis on ethnomathematics in mathematics education highlights the need to understand how future teachers perceive the relationship between mathematics and culture. This study explores the perspectives of pre-service mathematics teachers regarding their experiences and understanding of ethnomathematics through their formal instruction. While culturally responsive mathematics teaching has gained attention, limited research has focused on how these perspectives are shaped during teacher preparation. Most existing studies emphasize in-service teachers or curriculum, overlooking the formative experiences of pre-service teachers. Addressing this gap, this qualitative study investigates the reflections of nineteen pre-service teachers from four teacher education institutions in the Philippines. Guided by van Manen’s hermeneutic phenomenology and drawing on D’Ambrosio’s ethnomathematics framework and Vygotsky’s sociocultural theory, data were collected through structured open-ended questionnaires and follow-up interviews. Thematic analysis revealed two key themes: a shift from viewing mathematics as abstract and universal to seeing it as lived and culturally embedded; and a reimagining of mathematics education as inclusive, contextually relevant, and culturally responsive. Participants identified cultural practices such as weaving, farming, and traditional games as mathematical, though many did not specify the concepts involved. These findings suggest that introducing ethnomathematics during teacher preparation fosters critical reflection and supports the development of culturally responsive educators. Future research is needed to examine how these perspectives translate into classroom practice and to explore ways of sustaining culturally grounded mathematics instruction. This study contributes to the understanding of how teacher education programs can nurture culturally attuned mathematics teaching in diverse learning environments.